Isolation and TLC Densitometric Quantification of Lysergol from the Seeds of Ipomoea muricata (Linn.) Jacq. (22nd January 2013) - Patil, Shrikant; Nivsarkar, Manish; Anandajiwala, Sheetal
Abstract : Seeds of Ipomoea muricata, well known in Ayurveda for its purgative action, contains mainly indole alkaloids. Lysergol (major alkaloid) exhibits hypotensive, psychotropic, and uterus and intestine-stimulating properties. TLC fingerprint profile of I. muricata seeds was developed using chloroform : methanol (95 : 5 v/v) as the mobile phase. Plate was visualized under UV 254 nm and UV 366 nm and after derivatization with Van Urk reagent. Lysergol resolved at R f = 0.29 . Further, TLC-densitometric method was developed and validated for quantification of Lysergol avoiding derivatization step. Ethyl acetate :  methanol (7 : 3 v/v) was used as the mobile phase. Linear regression analysis data for the calibration curve showed a good linear relationship (r 2 = 0.9952 ) in the concentration range from 20 ng to 140 ng, with respect to the peak area. The developed method was precise with RSD for intraday (range from 1.20 to 1.89) and interday (range from 1.39 to 1.92) for 60, 80, and 100 ng/spot of Lysergol. The instrumental precision was 0.67 (% RSD). The limit of detection and limit of quantification for Lysergol were 12 ng and 40 ng, respectively. The average percentage recovery was 99.68. The amount of Lysergol was found to be 0.23% w/w. To the best of our knowledge, this is the first report for the quantification of Lysergol from I. muricata seeds without derivatization.